CORRELATION BETWEEN WEEKLY FORMATIVE AND SUMMATIVE ASSESSMENT OF MEDICAL STUDENTS IN MULTIDISCIPLINARY EXAMINATION AND ORAL EXAMINATION REPRODUCTIVE SYSTEM BLOCK - Nur Ramadani Meliani Syukri; Yuni Susanti Pratiwi; Eko Fuji Ariyanto; Muhammad Hasan Bashari; Achadiyani Achadiyani; Mohammad Ghozali; Putri Halleyana Rahman (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2021)
Background: The impact of weekly formative assessments on the summative performance of undergraduate medical students is not widely studied. The formative assessment began to be applied in the Undergraduate Medical Study Program, Faculty of Medicine, Padjadjaran University (Program Studi Kedokteran Fakultas Kedokteran Universitas Padjadjaran or PSK FK Unpad) in early 2020. This study aims to determine whether there is a correlation between weekly formative and summative assessment in Multidisciplinary Examination (MDE) and Structured Oral Examination (SOE).Methods: This study was conducted using a numerical correlative bivariate analysis with a cross-sectional design. The data used in this study was weekly formative assessment scores, MDE and SOE scores of Reproductive System (RPS) I and II of 138 medical student batch 2017. Results: Rank-Spearman test shows there was no significant correlation between the formative test scores and the MDE RPS I score (p>0.05) and the SOE score (p>0.05). Meanwhile, the MDE RPS II score with the formative test was found to be a significant correlation (p<0.05) and positively correlated (r=+0.211).Conclusion: This study shows that the use of weekly formative assessments might contribute to the students' achievement of MDE scores. Weekly formative assessments can be integrated into the curriculum of pre-clinical medical programs to improve student summative performance.